"Twice is Nice" Secondhand Clothing in Today's Global World. - PROŠIĆ-DVORNIĆ, MIRJANA (Bulletin of the Institute of Ethnography of the Serbian Academy of Sciences & Arts / Glasnik Etnografskog Instituta SANU, 2022)
Clothes, especially of high symbolic and/or material value, were always treasured and passed on to other users as gifts, heirlooms and legacies or given to charity, usually through religious institutions. Although secondhand clothing has a long history, it grew in volume and visibility with industrial revolution and the establishment of the consumer society, the driving force of capitalism. Desire to accumulate the new was always accompanied with the need to dispose of the old. Partly still maintaining charitable character, the global used-clothing exchange, starting with the 19th century rag trade international networks, has grown into a multi-billion-dollar commerce between the global North and the global South. While used clothes are still considered by some as trash, they can be a blessing to the world of the poor, a powerful (counter)-cultural declaration to some groups (e.g., hippies, grunge), or, if marketed as vintage, a deliberate fashion statement. Whatever the case, they present a "hot" controversial topic. Nowadays, the way secondhand is viewed and used around the world, proves again that globalization is a creative process producing always new forms of hybridization. This paper presents a short history and diverse views of the phenomenon. The research was based on multi-sited participant observation and interviews over an extended period of time.